Desa Adat sebagai Tameng Menuju Permohonan Dispensasi di Kabupaten Buleleng - Putu Andika Putra Diartawan (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Awig-Awig (traditional customary law) is a form of written customary law that exists and continues to develop within indigenous communities, particularly in Bali and Lombok. As part of Indonesia's pluralistic legal system, Awig-Awig plays a significant role in regulating social order, maintaining harmony, governing inter-community relations, and preserving local cultural and religious values. This study aims to examine the existence of Awig-Awig as a binding source of law within indigenous communities, as well as to analyze its relationship with the national legal system. The methods used in this research include juridical-normative and sociological approaches, supported by case studies conducted in several indigenous villages in Bali and Lombok. The results show that Awig-Awig remains highly relevant, respected, and effectively implemented as a community guideline. However, harmonization with state law is necessary to prevent potential norm conflicts and ensure legal certainty. These findings highlight the importance of formal recognition, protection, and integration of customary law within Indonesia’s national legal framework.